Contextualizing small business resilience during the COVID-19 pandemic: evidence from small business owner-managers - Hadjielias, Elias; Christofi, Michael; Tarba, Shlomo (My University, 2022)
In light of the unprecedented global crisis caused by the COVID-19 pandemic, resilient businesses are those more likely to make the transition to the post-COVID era. Our study draws on the concept of psychological resilience and focusses on individual owner-managers to the end of examining business resilience in the context of the COVID-19 pandemic. We conduct a longitudinal qualitative study, collecting data from 35 small business owner-managers between April and December 2020. Our findings—which provide insights into the micro-underpinnings of the resilience exhibited by small business in response to the COVID-19 pandemic—illustrate the responses and resilient qualities of owner-managers at both the personal and leadership levels, which facilitate resilient actions at the small business level. By drawing on a psychological perspective, our study provides a novel conceptualization of small business resilience at the person-role-organization nexus.